(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This study aimed to identify and analyze the features of women’s language used by Alexandra Cooper and Laverne Cox in the Call Her Daddy podcast, episode "Laverne Cox : Stop Taking Crumbs from Men" by applying the theory of women’s language features from Jennifer Coates (2013) to analyze the data. The method used in collecting data was documentation method and to analyzing the data was descriptive qualitative method. The results of the analysis were presented using an informal method, which was explained in the form of a description that was described in words. The results of the study showed that six features of women’s language are used by both speakers, such as minimal responses, hedges, tag questions, questions, swearing and taboo language, and compliments, while commands and directives are not found.